Exposure to Family Violence as a Predictor of Dating Violence and Child-to-Parent Aggression in Spanish Adolescents. (April 2017) - Izaguirre, Ainhoa; Calvete, Esther
Witnessing intimate partner violence (IPV) and child maltreatment may place children on a lifelong trajectory toward violence. The primary aim of this research was to examine the associations between exposure to violence at home and two forms of violence in close relationships in Spanish adolescents: child-to-parent violence (CPV) and dating violence. A sample of 845 adolescents (13-18 years) completed measures of direct victimization and witnessing of IPV, as well as adolescent dating violence and CPV at Time 1, and measures of adolescent dating violence and CPV 6 months later. Findings indicate that direct victimization is more relevant for later CPV than is witnessing IPV against the mother. Namely, direct victimization by the mother and father predicted an increase in child-to-mother and child-to-father violence over time. Witnessing IPV and direct victimization by the father predicted an increase in dating violence victimization in girls at Time 2.